Rescue effect drives local persistence of fish species in the Upper Paraná River floodplain. (8th February 2021) - Granzotti, Rafaela V.; Cassemiro, Fernanda A. S.; Agostinho, Angelo A.; Bini, Luis M.
Abstract: The interspecific variation in spatial distribution has been frequently studied in macroecology, but cross‐species differences in temporal occupancy (the number of times a species has been recorded in a site, i.e. local persistence) are seldom investigated. Here we aim to determine the relative importance of different predictors of species temporal occupancy, including local abundance, body size, range size, biological traits, environmental niche metrics, and proportion of the sites occupied (mean landscape occurrence). Using 17 years of data on 93 Neotropical fish species collected at the Upper Paraná River floodplain, we modelled temporal occupancy in six floodplain lakes, controlling for phylogenetic dependence, and investigated whether the relative importance of predictors was maintained across sites. Mean landscape occurrence and mean local abundance were the main predictors of temporal occupancy in all six lakes. Body size was also important in most lakes. The concordance in the ranks of predictors was high, indicating consistency in the mechanisms behind temporal occupancy across sites. Our results indicate the importance of metapopulation processes, especially the rescue effect, in determining long‐term persistence of fish local populations in floodplains. The influence of spatial occupancy on local persistence implies that protecting a large number of habitats in the landscape might reduce the risk of local extinction of species, thus maintaining biodiversity levels in the system.